Medical-demographic problems of Ukraine and some ways of their overcoming. - Yeroshkina, T. V.; Derevyanko, D. V. (Medicni Perspektivi, 2018)
The article covers the main medical and demographic problems of Ukraine: birth-rate decline, growth of mortality; moving of qualified personnel abroad, which led to a decrease in the population over the years of independence by more than 9.5 million people. The total birth rate in Ukraine in 2017 was 10.3 per 1000 people, which is 14.9% lower than in 1991. The lowest birth rate was observed in 2000-2002 (7.8, 7.7, 8.1). Then gradually there is an increase in the indicators in 2012 - 11.4 per 1000 people. The total mortality rate in 2017 is 14.4, which is 11.6% higher than in 1991. According to the analysis period, the lowest mortality rate was registered in 1991 - 12.9%. The most high-speed in the period 2005-2008. (16.6, 16.2, 16.4). The natural increase from -0.8 dropped to-4.1 (more than 5 times). The demographic situation in Ukraine is characterized by depopulation, it is characterized by demographic crisis, the main features of which are adverse changes not only in the number but also in the healthy of population, which is manifested in the decrease in the average life expectancy, the deterioration of the health of children and adolescents, the growth of malformations among newborns, high mortality rates from circulatory system diseases; oncological diseases, injuries, poisonings and other consequences of external causes; men's super mortality. The main causes of these phenomena are the protracted economic crisis, the ecological catastrophe (Chernobyl), the country's being in a state of hybrid war, which led to a sharp decline in living standards, uncertainty of the population in the future deaths of people. We offered some ways to over come the country's demographic crisis.